"One Hour He Is a Christian and the Next He Is a Muslim!" A Family Dispute from the Cairo Geniza. Issue 1 (2nd January 2019) - Zinger, Oded
ABSTRACT: This study publishes a newly identified letter to Moses Maimonides reconstructed from three Geniza fragments. The letter describes an inheritance dispute over real estate in the Egyptian delta town of al-Maḥalla. Having a letter written by a litigant provides information on what took place outside of court, information that is often missing from legal records. This allows us to explore the dynamics of a dispute in which one side makes a legal move, and the other counters with a move outside of court, and vice versa. These manoeuvrings included action in Jewish and Muslim courts, appeal to a jurisconsult, social pressure and performative disregard to the boundaries of the religious communities. As a result, we can conceive of the legal arena not only as encompassing different legal institutions but also as a social space constituted by the ways litigants experienced and interacted with legal institutions.